If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) = 40 Reorder the terms: 2(3 + x) = 40 (3 * 2 + x * 2) = 40 (6 + 2x) = 40 Solving 6 + 2x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2x = 40 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 40 + -6 2x = 40 + -6 Combine like terms: 40 + -6 = 34 2x = 34 Divide each side by '2'. x = 17 Simplifying x = 17
| 9x^2-10=890 | | 2(w)2(w)=64 | | 5y+10=8y+5 | | 3-wi/5i | | 4x/7=6x/7-28 | | 2y+2+3y-9=180 | | 0=5y+5-x | | -4x-3(6-7x)=-18+3x | | 8(x+13)+(1712-1600)=13088 | | (2x-1)/(x-4) | | z^2+(2i-7)z+13-i=0 | | 60+1=7c | | 1/4a-1/8a | | (5+x)2=24 | | X^3+12*x^2-45*x+242=0 | | 9z^2+18z-135= | | -m^2+mn+2m-2n= | | 4x^2-5x=150 | | 2xy-3y+x-41= | | -3+x-38= | | u^2-16uv+64v^2=0 | | (G+4)-3g=1+a | | 123+32-200= | | -3+x=38 | | D^2-34=0 | | 4-(4d+3)=8d-3(d+13) | | D^2-32=0 | | -8x-(-12)=2x+11 | | 4x^2-5x-150=0 | | -1.4m+0.1=-4.9m^2 | | 2y-10+3x=0 | | 7(c+4)=56 |